Clinical supervision and counseling psychology in the Republic of Ireland. Issue 2 (2nd July 2016) - Creaner, Mary; Timulak, Ladislav
Abstract : Against the background of political, social, economic, and cultural factors, we present an overview of clinical supervision within counseling psychology in the Republic of Ireland (ROI). Clinical supervision has been an integral aspect of counseling psychology training in the ROI since its inception, and more recently it is being promoted as a professional support over the course of the counseling psychologist's career. Within this context, we discuss the current status of clinical supervision, including the major developments, key policies, and best practice principles. Recommendations regarding the future direction of clinical supervision in the ROI and globally are also offered.